2015
DOI: 10.3727/096368915x687219
|View full text |Cite
|
Sign up to set email alerts
|

Systemic and Local Administration of Allogeneic Bone Marrow-Derived Mesenchymal Stem Cells Promotes Fracture Healing in Rats

Abstract: Mesenchymal stem cells (MSCs) are immune privileged and a cell source for tissue repair. Previous studies showed that there is systemic mobilization of osteoblastic precursors to the fracture site. We hypothesized that both systemic and local administration of allogeneic MSCs may promote fracture healing. Bone marrow-derived MSCs and skin fibroblasts were isolated from GFP Sprague–Dawley rats, cultured, and characterized. Closed transverse femoral fracture with internal fixation was established in 48 adult mal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
48
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 70 publications
(52 citation statements)
references
References 37 publications
1
48
0
3
Order By: Relevance
“…The disease is widely observed on a global scale, and is the primary cause of fractures and bone loss, and seriously threatens human health (1). The suppression of bone-forming ability is the main pathogenesis of the disease.…”
Section: Introductionmentioning
confidence: 99%
“…The disease is widely observed on a global scale, and is the primary cause of fractures and bone loss, and seriously threatens human health (1). The suppression of bone-forming ability is the main pathogenesis of the disease.…”
Section: Introductionmentioning
confidence: 99%
“…Systemic injection of MSCs has been used in the treatment of osteoporosis and fracture healing for many years [Huang et al, 2015]. Several factors are involved in order to achieve more successful results from cell therapy in bone healing.…”
Section: Systemic Injection Approachmentioning
confidence: 99%
“…Mesenchymal stromal cells (MSCs) have potentials for bone regeneration [1][2][3]. Previous reports indicated that MSCs could repair damaged tissue by replacing damaged cells [3].…”
Section: Introductionmentioning
confidence: 99%